Restructuring and Insolvency in Europe : Policy Options in the Implementation of the EU Directive - Garrido, Jose (IMF Working Papers; Working Paper ;, 2021)
The Directive on Restructuring and Insolvency sets minimum standards for restructuring and certain insolvency matters, but its harmonization effect will be limited given multiple options for implementation, likely leading to divergent restructuring models in Europe. These options reveal different policy approaches to the regulation of restructuring and insolvency. The analysis in this paper aims to illustrate the breadth of the policy choices and their consequences for restructuring activity. States should carefully design restructuring procedures to avoid the negative economic effects of certain options that could undermine creditors' rights or result in unpredictable outcomes, particularly in cross-border cases.